RANCANG BANGUN ALAT KONVEYOR PADA MESIN PENGGILING PADI - Nurul Azizah Tamher; Andriyono Andriyono; Wahida Wahida (Musamus AE Featuring Journal, 2021)
This research aims to design a conveyor on a rice grinder and determine the capacity when the conveyor process works. The research was conducted at the Mopah Lama workshop in Merauke. This study used an experimental method by designing the shape of a conveyor for a rice grinding machine and then proceeding to test the tool by observing parameters or measuring predetermined variables. This research produced a conveyor that was in accordance with the design and dimensions of the tool with a slope of 45O, a length of 2.98 cm, a width of 30 cm, and a height of 2.60 cm. The results showed that at the engine speed of 1500 rpm and the screw conveyor 112.5 rpm, the average working capacity of the tool was 384 kg/hour, with the average grain peeling being 0.6 kg/hour. At the engine speed of 1700 rpm and the screw conveyor 127.5 rpm, the average working capacity of the tool was 522 kg/hour with the average flaking of the grain of 3.72 kg/hour, and at the engine speed of 1900 rpm and screw conveyor 142.5 rpm, the average working capacity of the tool was 603.6 kg/hour with the average grain exfoliation of 6.6 kg/hour. This tool will work effectively at low rotational speeds.